2017
DOI: 10.1007/s10856-017-5893-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug loaded microbeads entrapped electrospun mat for wound dressing application

Abstract: A new design of antibiotic loaded wound dressing and its initial in vitro evaluation is described. Chitosan microbeads loaded with ampicillin were sandwiched within polycaprolactone electrospun mat (MbAPPCL). The morphology was analyzed by scanning electron microscopy and surface chemistry was characterized by Fourier Transform Infrared Spectroscopy. In vitro cytotoxicity using L-929 fibroblast cells by direct contact test and elution assay revealed non-cytotoxic nature of MbAPPCL. The cell adhesion and viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A susceptibility test of MbAPPCL to Staphylococcus aureus also showed its excellent antibacterial properties. 128 …”
Section: Biological and Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A susceptibility test of MbAPPCL to Staphylococcus aureus also showed its excellent antibacterial properties. 128 …”
Section: Biological and Medical Applicationsmentioning
confidence: 99%
“…The hemolysis rate and platelet adhesion rate indicated that MbAPPCL had blood compatibility. A susceptibility test of MbAPPCL to Staphylococcus aureus also showed its excellent antibacterial properties 128.…”
mentioning
confidence: 98%
“…Better strategy is to coat a candidate barrier material with Lys‐PDA so that the surface gets functionalized . Previously standardized procedures were utilized to synthesize nanofibrous PCL membrane resembling the structural component of ECM . PCL is an FDA approved, biodegradable linear polyester, which can be tuned to improve surface properties to suit the biological needs .…”
Section: Discussionmentioning
confidence: 99%
“…28 Previously standardized procedures were utilized to synthesize nanofibrous PCL membrane resembling the structural component of ECM. 28,40 PCL is an FDA approved, biodegradable linear polyester, which can be tuned to improve surface properties to suit the biological needs. 41 Peptide functionalization can be utilized to impart cell adhesive properties to the PCL mats.…”
Section: Discussionmentioning
confidence: 99%
“…9 A 10% PCL (average Mn 80000, Sigma) solution was prepared using a binary solvent system of Terahydrofuran and Dimethyl sulphoxide. The polymer was taken in a syringe with a blunt end needle and connected to a customized electrospinning setup (Holmarc Opto-Mechatronics Pvt Ltd, India).…”
Section: Fabrication Of Electrospun Matsmentioning
confidence: 99%